From Conflict to Assimilation: Strategies of Muslim Immigrants in Papua Special Autonomy Era - F. Faisal; Abdul Munir Mulkhan; Achmad Nurmandi; Hasse Jubba (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2019)
This paper aims to explain the forms of Muslim immigrant strategies in Papua in the era of special autonomy. After the implementation of special autonomy in Papua, migrants feel the increasing tension or competition in the economic and political fields. Data obtained through the method of observation, interviews, and literature studies. Observations focused on the economic practices of Muslim migrants in places such as the market in Jayapura, Papua. Interviews were conducted with a number of parties, both Muslim migrants and local Papuans, to obtain information on many things including their response to the presence of Muslim migrants. In addition, data was also obtained through the documentation of literature related to the topic of this paper. The data obtained were then analyzed through the steps of qualitative analysis, namely data reduction, data presentation, drawing conclusions/verification. This paper confirms that Muslim migrants made various efforts to deal with various obstacles in the era of Special Autonomy in Papua in three ways. First, Muslim migrants strengthen the economy, especially the informal sector. Secondly, the political sector is not the main objective of the existence of Muslim migrants. Third, Muslim migrants are not exclusive, especially in establishing communication with indigenous people.